1999
DOI: 10.1021/js9900856
|View full text |Cite
|
Sign up to set email alerts
|

Solubility parameters as predictors of miscibility in solid dispersions

Abstract: This paper reports interactions and possible incompatibilities in solid dispersions of hydrophobic drugs with hydrophilic carriers, with solubility parameters employed as a means of interpreting results. Systems containing ibuprofen (IB) and xylitol (XYL) in varying proportions and systems of IB with other sugars and a sugar polymer were produced using solvent evaporation and fusion methods. Additionally, bridging agents were employed with IB/XYL systems to facilitate the production of a solid dispersion. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
341
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(351 citation statements)
references
References 33 publications
10
341
0
Order By: Relevance
“…The miscibility limit of nifedipine/soluplus co-precipitates was reported to be 30% w/w drug loading, using different preparation methods (freeze drying, melting and solvent evaporation) [12] . These values agree with what predicted by the Hildebrand's solubility parameters: the carriers used to prepare co-precipitates and nifedipine display Δδ values well below the critical limit [21,22] (Table 2). These values indicate likely miscibility and make it possible to predict the formation of a homogeneous dispersion of the drug into the carriers; while for the sucrester it could be expected that the drug could be present partly in undissolved/re-precipitated form, being borderline the δ value reported for the sucrester P1670 [23] .…”
Section: Figure 1 (Abcd): Sem Imagessupporting
confidence: 85%
“…The miscibility limit of nifedipine/soluplus co-precipitates was reported to be 30% w/w drug loading, using different preparation methods (freeze drying, melting and solvent evaporation) [12] . These values agree with what predicted by the Hildebrand's solubility parameters: the carriers used to prepare co-precipitates and nifedipine display Δδ values well below the critical limit [21,22] (Table 2). These values indicate likely miscibility and make it possible to predict the formation of a homogeneous dispersion of the drug into the carriers; while for the sucrester it could be expected that the drug could be present partly in undissolved/re-precipitated form, being borderline the δ value reported for the sucrester P1670 [23] .…”
Section: Figure 1 (Abcd): Sem Imagessupporting
confidence: 85%
“…48,49 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Quantification analysis for the composite systems was performed by DVS and NIR due to their enhanced sensitivity at detecting low amorphous content levels, compared to DSC and pXRD.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of cocrystals success rate was improved by using the components which have similar miscibility [67] . It was demonstrated that the two components should be miscible if total HSPs difference was <7MP a 0.5 , otherwise immiscible [68] . Another method estimates the miscibility of two components if the difference is ≤5 MP 0.5 between two substances which are supposed to be cocrystal formation [69,70] .…”
Section: Hansen Solubility Parametermentioning
confidence: 99%